Addressing critical gaps in the treatment of eating disorders. Issue 3 (19th January 2017) - Kazdin, Alan E.; Fitzsimmons‐Craft, Ellen E.; Wilfley, Denise E.
Abstract: Remarkable progress has been made in developing psychosocial interventions for eating disorders and other mental disorders. Two priorities in providing treatment consist of addressing the research‐practice gap and the treatment gap. The research‐practice gap pertains to the dissemination of evidence‐based treatments from controlled settings to routine clinical care. Closing the gap between what is known about effective treatment and what is actually provided to patients who receive care is crucial in improving mental health care, particularly for conditions such as eating disorders. The treatment gap pertains to extending treatments in ways that will reach the large number of people in need of clinical care who currently receive nothing. Currently, in the United States (and worldwide), the vast majority of individuals in need of mental health services for eating disorders and other mental health problems do not receive treatment. This article discusses the approaches required to better ensure: (1) that more people who are receiving treatment obtain high‐quality, evidence‐based care, using such strategies as train‐the‐trainer, web‐centered training, best‐buy interventions, electronic support tools, higher‐level support and policy; and (2) that a higher proportion of those who are currently underserved receive treatment, using such strategies as task shifting and disruptive innovations, including treatment delivery via telemedicine, the Internet, and mobile apps.